2021
DOI: 10.3748/wjg.v27.i48.8201
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoylation in Crohn’s disease: Current status and future directions

Abstract: S-palmitoylation is one of the most common post-translational modifications in nature; however, its importance has been overlooked for decades. Crohn’s disease (CD), a subtype of inflammatory bowel disease (IBD), is an autoimmune disease characterized by chronic inflammation involving the entire gastrointestinal tract. Bowel damage and subsequent disabilities caused by CD are a growing global health issue. Well-acknowledged risk factors for CD include genetic susceptibility, environmental factors, such as a we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…This collection of palmitoylated proteins is referred to as the “palmitoylome,” and >600 substrates have been identified and characterized so far (Jin et al, 2021 ). Various techniques have been used to detect S‐palmitoylation including acyl‐biotin exchange (ABE), acyl‐resin‐assisted capture (Acyl‐Rac), and acyl‐PEG exchange (APE) followed by LC–MS/MS (Cheng et al, 2021 ; Jeong et al, 2023 ; Ji et al, 2013 ). The dysregulation of protein S‐palmitoylation has been linked to the development of various human diseases, including viral infections, cancer, diabetes, as well as immunological and neurological disorders.…”
Section: Integration Of Various Omics Techniquesmentioning
confidence: 99%
“…This collection of palmitoylated proteins is referred to as the “palmitoylome,” and >600 substrates have been identified and characterized so far (Jin et al, 2021 ). Various techniques have been used to detect S‐palmitoylation including acyl‐biotin exchange (ABE), acyl‐resin‐assisted capture (Acyl‐Rac), and acyl‐PEG exchange (APE) followed by LC–MS/MS (Cheng et al, 2021 ; Jeong et al, 2023 ; Ji et al, 2013 ). The dysregulation of protein S‐palmitoylation has been linked to the development of various human diseases, including viral infections, cancer, diabetes, as well as immunological and neurological disorders.…”
Section: Integration Of Various Omics Techniquesmentioning
confidence: 99%
“…Dextran sulfate sodium-induced colitis in mice is reduced by treatment with the APT2 inhibitor ML349 and Zdhhc7 knockout [121]. Therefore, the STAT3 S-palmitoylation/de-palmitoylation cycle could be a target for Th17-related immune disorders, suggesting that inhibition of STAT3 S-palmitoylation/de-palmitoylation can be a potential therapeutic strategy for IBD [121,155].…”
Section: S-palmitoylation and Disease Relevancementioning
confidence: 99%
“…Environmental influences, genetic factors, and abnormal infections often contribute to inducing AIDs. Multiple studies have indicated that NOD1 and NOD2 polymorphisms are involved in a variety of AIDs, including Crohn's disease, Blau syndrome, Behcet's syndrome, atopic diseases, and early-onset sarcoidosis [155][156][157]. CD-associated NOD2-loss-of-function variants with reduced Spalmitoylation levels lead to less NOD2-membrane association and are incapable of NOD2 signaling, while the increased Spalmitoylation of early-onset sarcoidosis-or BS-associated NOD2 gain-of-function mutants drives NF-κB hyperactivity [112,158].…”
Section: S-palmitoylation and Disease Relevancementioning
confidence: 99%
“…Numerous pro‐inflammatory genes that encode cytokines, chemokines, and adhesion molecules crucial for inflammation and immunological responses are stimulated by NF‐κB 132 . The NF‐κB signalling pathway regulates the expression of TNF‐α, IL‐1, IL‐6, IL‐12, IL‐23, and IκBa 133 . Anti‐TNF antibodies, including infliximab, adalimumab, and certolizumab, 134–136 are a first‐line treatment for CD and several other autoimmune illnesses 137 .…”
Section: Prospective CD Therapies Targeting Enteric Glial Cells and M...mentioning
confidence: 99%
“…Anti‐TNF antibodies, including infliximab, adalimumab, and certolizumab, 134–136 are a first‐line treatment for CD and several other autoimmune illnesses 137 . Other biologic medications include IL‐12/23 antibodies, e.g., ustekinumab, 138 and corticosteroids, which exert immunosuppressive effects by increasing IκBα, a crucial component of the NF‐κB pathway 133 . In addition to immunomodulatory effects, anti‐TNF therapy could increase IL‐22 production in patients with CD and consequently promote intestinal epithelial barrier restoration 139 .…”
Section: Prospective CD Therapies Targeting Enteric Glial Cells and M...mentioning
confidence: 99%